Poverty Alleviation Policies of Selected Churches in Anambra State, Nigeria - Duke , Emmanuel Orok; Okafor, Justus Onyebuchi (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
Poverty is a social problem. Its alleviation has been one of the major issues that occupy a significant place in the scale of preference of developmental policies of several nations, international organizations, church and other interested stakeholders. Thus, the thrust of this work centers on poverty alleviation strategies of selected Churches in Anambra State: namely how this institution participates in some economic activities, skill acquisition programmes, and empowerment programmes, among others in view of controlling the scourge of poverty. The research methods employed here are: both qualitative and quantitative - survey and documentary research methods of data collection. The survey method collects data through designed research questionnaire and oral interview with some respondents respectively, while in qualitative approach is the content analysis of written sources such as books, journal articles and online sources that are relevant to the research. The findings of this research show that poverty is human-induced problem manifested in the mismanagement of resources and other forms of ills. Selected churches in Anambra State has reduced the effects of poverty through its collaboration with the State and Non-Governmental Organizations in poverty reduction programmes.